Temperature Dependent Control of the R27 Conjugative Plasmid Genes - Gibert, Marta; Paytubi, Sonia; Madrid, Cristina; Balsalobre, Carlos (Frontiers in Molecular Biosciences, 2020)
Conjugation of R27 plasmid is thermoregulated, being promoted at 25ºC and repressed at 37ºC. Previous studies identified plasmid-encoded regulators, HtdA, TrhR and TrhY, that control expression of conjugation-related genes (tra). Moreover, the nucleoid-associated protein H-NS represses conjugation at non-permissive temperature. A transcriptomic approach has been used to characterize the effect of temperature on the expression of the 205 R27 genes. Many of the 35 tra genes, directly involved in plasmid-conjugation, were upregulated at 25ºC. However, the majority of the non-tra R27 genes – many of them with unknown function – were more actively expressed at 37ºC. The role of HtdA, a regulator that causes repression of the R27 conjugation by counteracting TrhR/TrhY mediated activation of tra genes, has been investigated. Most of the R27 genes are severely derepressed at 25ºC in an htdA mutant, suggesting that HtdA is involved also in the repression of R27 genes other than the tra genes. Interestingly, the effect of htdA mutation was abolished at non-permissive temperature, indicating that the HtdA-TrhR/TrhY regulatory circuit mediates the environmental regulation of R27 gene expression. The role of H-NS in the proposed model is discussed.